2008
DOI: 10.1007/s10681-008-9673-x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding potential of Solanum tuberosum–S. commersonii pentaploid hybrids: fertility studies and tuber evaluation

Abstract: Twenty-one (near) pentaploid hybrids between sexually incompatible Solanum commersonii [2x(1EBN)] and cultivated S. tuberosum [4x(4EBN)] were characterized for tuber traits and fertility. A number of genotypes resembled the S. tuberosum type in terms of stolon length and eye depth and produced tubers under long day conditions. Tuber yields were not as high as expected, probably due to lack of adaptation of the S. commersonii genome to the environmental conditions in southern Italy (on average 325 gÁpt -1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Due to the good fertility of (near) pentaploids (Caruso et al 2008), there should be no further barrier to the introgression of resistance genes into cultivated varieties. This plant material is also suitable for further studies on the genetics and nature of R. solanacearum resistance of wild S. commersonii.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the good fertility of (near) pentaploids (Caruso et al 2008), there should be no further barrier to the introgression of resistance genes into cultivated varieties. This plant material is also suitable for further studies on the genetics and nature of R. solanacearum resistance of wild S. commersonii.…”
Section: Discussionmentioning
confidence: 99%
“…2 will hybridize with cultivated potato, producing generally fertile aneuploids. Several variations of this scheme have been published (Ehlenfeldt and Hanneman, 1984; Camadro and Espinillo, 1990; Adiwilaga and Brown, 1991; Carputo et al, 1997; Carputo and Barone, 2005; Caruso et al, 2008). Ploidy reduction can also be used to manipulate EBN.…”
Section: Introgression Of Wild Species Into Cultivated Potatomentioning
confidence: 99%
“…Although triploids are often sterile or nearly so, odd ploidy levels are not always a guarantee of seedlessness. Higher-level polyploids, such as pentaploids, vary in fertility levels, as observed in crops such as Solanum (Caruso et al, 2008), Lantana (Czarnecki et al, 2014), and Vaccinium (Laverty and Vorsa, 1991). For example, Lantana triploids had only 9.3% pollen stainability compared with 34.6% in pentaploids (Czarnecki et al, 2014).…”
mentioning
confidence: 99%
“…For example, Lantana triploids had only 9.3% pollen stainability compared with 34.6% in pentaploids (Czarnecki et al, 2014). In Solanum, Caruso et al (2008) found that several pentaploid hybrids were female fertile when crossed with the tetraploid S. tuberosum. In addition, they found that the number of extra chromosomes in their aneuploid accessions had a significant effect on most of their fertility parameters, including berry set, number of seeds per berry, and number of seeds per pollinated flower (Caruso et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation